2021
DOI: 10.3389/fcell.2021.615569
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxidative Stress and Ca2+ Signaling in Psychiatric Disorders

Abstract: Psychiatric disorders are caused by complex and diverse factors, and numerous mechanisms have been proposed for the pathogenesis of these disorders. Accumulating evidence suggests that oxidative stress is one of the general factors involved in the pathogenesis/pathophysiology of major psychiatric disorders, including bipolar disorder, depression, anxiety disorder, and schizophrenia. Indeed, some clinical trials have shown improvement of the symptoms of these disorders by antioxidant supplementation. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 138 publications
0
9
0
Order By: Relevance
“…We now turn our attention to the therapeutic potential of targeting brain redox and immune biology in SZ. Preclinical studies using animal models, as well as patient-derived blood and CSF studies, have identified some intriguing targets relevant to both processes ( Perkins et al, 2015 ; Kim et al, 2019 ; Nakao et al, 2021 ; Cuenod et al, 2022 ). These include the GSH/GPX/Gred and TRX/PRX/SRX systems, the NAD/NADH system, the MMP9/RAGE pathway, and bioenergetics-related micro-RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…We now turn our attention to the therapeutic potential of targeting brain redox and immune biology in SZ. Preclinical studies using animal models, as well as patient-derived blood and CSF studies, have identified some intriguing targets relevant to both processes ( Perkins et al, 2015 ; Kim et al, 2019 ; Nakao et al, 2021 ; Cuenod et al, 2022 ). These include the GSH/GPX/Gred and TRX/PRX/SRX systems, the NAD/NADH system, the MMP9/RAGE pathway, and bioenergetics-related micro-RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PPA oxidative stress causes membrane abnormalities in L -type calcium channels that directly affect the channel's shape or the number of channels, which results in an increase in calcium overload and brain malfunction. More evidence for the role of Calcium Channel Genes in ASD stems from the association of ASD with single-nucleotide polymorphism in the CACNA1C gene encoding a T-type Ca 2+ channel subunit [37] .…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of BD is still unknown, but family studies as well as adoption and twins studies suggest significant contribution of genetic factors 22 . In addition, evidence suggests that altered signaling pathways, including oxidative stress, is one of the general factors involved in the pathogenesis/neurobiology of BD 6 . Reactive oxygen species (ROS) are involved in induction of expression of the p53 tumor suppressor gene and cell aging.…”
Section: Discussionmentioning
confidence: 99%
“…One of the factors involved in activating these signaling pathways and apoptosis is oxidative stress 4 . Several studies have indicated that oxidative stress parameters including nitric oxide levels, antioxidant enzymes, and lipid peroxidation have been altered in patients with BD 5 , 6 . Rising evidence currently has shown long noncoding RNAs (lncRNAs) have a relevant function in the cellular response to DNA damage and oxidative stress 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%